Men and art. (New York : Studio Publishers, 1958)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : ?
Redactie : Studio Publishers, 400 West 57th Street New York 19
Engels
Periodiek